2016
DOI: 10.1038/srep29836
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Comparison of Photothermal Heat Generation between Gold Nanospheres and Nanorods

Abstract: Gold nanoparticles (GNPs) are widely used for biomedical applications due to unique optical properties, established synthesis methods, and biological compatibility. Despite important applications of plasmonic heating in thermal therapy, imaging, and diagnostics, the lack of quantification in heat generation leads to difficulties in comparing the heating capability for new plasmonic nanostructures and predicting the therapeutic and diagnostic outcome. This study quantifies GNP heat generation by experimental me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
136
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(148 citation statements)
references
References 63 publications
5
136
1
Order By: Relevance
“…With regard to the size homogeneity effect, our results revealed that D P affected not only the alteration of the light attenuation within the medium, but also the plasmonic heat power generation. Notably, a high GNS D P is a considerable hindrance to increasing the temperature by PPT heating, contrary to the results reported by Qin et al Based on these results, the S‐GNSs were verified to enhance the plasmonic heat power by 20.6%, due to both the increased shape uniformity and size homogeneity effects compared to the O‐GNSs. Thus, we envision that a shape closer to an ideal sphere will result in a greater heating temperature, and that size control toward monodispersity is another important factor in enhancing photothermal efficiency by controlling the nanostructural shape.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…With regard to the size homogeneity effect, our results revealed that D P affected not only the alteration of the light attenuation within the medium, but also the plasmonic heat power generation. Notably, a high GNS D P is a considerable hindrance to increasing the temperature by PPT heating, contrary to the results reported by Qin et al Based on these results, the S‐GNSs were verified to enhance the plasmonic heat power by 20.6%, due to both the increased shape uniformity and size homogeneity effects compared to the O‐GNSs. Thus, we envision that a shape closer to an ideal sphere will result in a greater heating temperature, and that size control toward monodispersity is another important factor in enhancing photothermal efficiency by controlling the nanostructural shape.…”
Section: Discussioncontrasting
confidence: 68%
“…Wang et al showed that gold nanocages obtained a higher PTCE per gold atom than GNRs and gold nanohexapods upon laser irradiation with a central wavelength of 808 nm . Qin et al more recently demonstrated that the dispersity of GNPs is also an important metric for generating plasmonic photothermal (PPT) heat and showed that it significantly affected GNRs more than gold nanospheres (GNSs) . These studies provided valuable data for selecting the correct size and shape of GNPs to obtain enhanced performance in various applications.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, many of these models, even if they are targeted toward specific tumor mass, may face challenges in confining heat production at the very local levels; studies show that during the photothermal treatments of the cells using the nanoparticles, the temperature of the entire field is raised by a significant amount. [48][49][50][51] This could raise serious concerns about damage upon nearby, non-targeted tissue as the entire field is being affected. Our method tries to overcome this drawback by promoting target-specific attachment of the nanoparticle products to the tumor: This had led to dramatic reduction in overall heat generation of the field (Figure 5), while producing enough thermal energy at proximity to the target to induce sufficient damage on the tumor while minimizing temperature change.…”
Section: Discussionmentioning
confidence: 99%
“…The photothermal conversion efficiency of AuNPs of different sizes and shapes, and how this measurement can be determined, has been extensively studied in literature, and we point the reader towards these published works for more in-depth discussion. 13,15,23,24 In general, for spherical AuNPs, those with smaller diameters have higher conversion efficiency than those with larger diameters. Additionally, non-spherical AuNP designs, including NRs, nanostars, and NCs, are more efficient photothermal transducers than their spherical counterparts like NSs due to their larger absorption cross sections.…”
Section: Introductionmentioning
confidence: 99%